Three Canadian Sephardic Women and their Transplanted Repertories: From Salonica, Larache and Sarajevo to Montreal and Kahanawá:ke - Cohen, Judith R. (Folk Music, Traditional Music, Ethnomusicology: Canadian Perspectives Past and Present, 2007)

Identifications, relations et circulation des savoirs chez les Atikmakekw de la Haute-Mauricie. Un regard ethnographique sur le tewehigan - Jérôme, Laurent (La nature des esprits dans les cosmologies autochtones, 2007)

Essential Song: Three Decades of Northern Cree Music - Whidden, Lynn (Wilfrid Laurier University Press, 2007)
A pack that contains a book and a CD. The book presents an outline of Cree musical history and a contribution to ethnomusicology, social history, and Aboriginal studies. The CD contains over 80 Cree hunting songs.